REPRODUCTIVE INTENTION AMONG URBAN YOUNG WOMEN: THE INTERPLAY OF PERCEIVED ANOMIE, ECOLOGICAL VALUES, AND READINESS FOR FAMILY LIFE - Adhitiah, Eka Fitriany Putri; Sunarti, Euis; Muflikahti, Istiqlaliyah (Universitas Airlangga, 2025)
The decline in reproductive intention among urban young women, as reflected in Indonesia’s Total Fertility Rate decreasing to 1.96 in 2024, illustrates a broader demographic transition. This phenomenon necessitates a conceptual shift beyond demographic explanations, urging the inclusion of sociopsychological dimensions in understanding reproductive intentions. This study aims to analyze the influence of perceived anomie, ecological attitudes, and family readiness on reproductive intention. A survey was conducted among 336 young women in the Greater Jakarta area (Jabodetabek) using a voluntary sampling approach and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that reproductive intention is relatively low. Family readiness was found to strengthen reproductive intention, whereas higher levels of perceived anomie and ecological attitudes reduced it. Conversely, perceived anomie increased ecological attitudes, and ecological attitudes positively influenced family readiness. These findings suggest that women with a high level of ecological awareness tend to demonstrate readiness for long-term relationships, yet simultaneously develop hesitancy toward reproductive decisions in the context of perceived ecological crisis and anomie. Strengthening interventions that support family readiness among young women is essential, particularly through approaches that are responsive to social uncertainty and integrative of sustainability values in reproductive planning processes.